2023
DOI: 10.1017/jfm.2023.89
|View full text |Cite
|
Sign up to set email alerts
|

Viscous effects in Mach reflection of shock waves and passage to the inviscid limit

Abstract: The influence of viscosity on the Mach reflection of shock waves in a steady flow of a monatomic gas is studied by solving the Navier–Stokes equations numerically. Based on the nested block grid refinement technique, the flow near the shock wave intersection is simulated, and its behaviour with increasing Reynolds number is studied. The computations are performed for the interaction of both strong (free-stream Mach number $M_\infty = 4$ ) and weak ( $M_\infty = 1.7$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…2010; Shoev et al. 2023) (this term was originally coined for the flow near the triple point in the irregular shock reflection). Indeed, the temperature value behind two oblique shocks given by RH conditions correspond to the orange colour in the legend.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2010; Shoev et al. 2023) (this term was originally coined for the flow near the triple point in the irregular shock reflection). Indeed, the temperature value behind two oblique shocks given by RH conditions correspond to the orange colour in the legend.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, they all predict the appearance of a 2-D maximum (overshoot) to the right of the point (0, 0). The zone with the temperature maximum behind the RS is called the non-RH zone (Sternberg 1959;Ivanov et al 2010;Shoev et al 2023) Ivanov et al 2012;Timokhin et al 2015). In addition, it was shown that this maximum is observed at all types of molecular interaction potentials with the Mach number Ma ≥ 3.9 (Yen 1984;Erofeev & Friedlander 2002).…”
Section: General Features Of Flow Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the above two points, how dissipative processes and finite shock thickness reshape the flow field of multi-dimensional shock systems (e.g. the viscous effect in Mach reflection of shock waves Shoev et al 2023) is also of interest.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This inherently can lead to deviations between model predictions and observations of field data, and to sub-optimal target values. Studies have shown [4,5], that the power loss of the un-waked turbine depends on the inflow condition, control strategy [6], and varies when the turbine is waked [7]. Additionally, the dependency of the wake characteristics on the incoming inflow condition, e.g.…”
Section: Introductionmentioning
confidence: 99%